Managerial multi-tasking, Team diversity, and mutual fund performance - Chen, Jean Jinghan; Xie, Li; Zhou, Si (Journal of Corporate Finance, 2020)
This study examines the impact of multi-tasking teams on fund performance. We find that while managerial multi-tasking has a negative impact on fund performance, teamwork can mitigate the adverse effect associated with managerial multi-tasking, which is indicative of superior performance of funds managed by multi-tasking teams. More importantly, it is the characteristics of the multitasking team that contribute to these superior results, which can be attributed to network cognitive diversity, suggesting that extended networks, facilitated by indirectly-connected managers via local teammates, can largely enhance the scale of cognitive diversity, thus generating significant gains through information pooling and integration. In assessing possible mechanisms for the observed superior performance, we find evidence of improved decision-making induced by network cognitive diversity through both transmission and sharing of value-relevant information, and speedy information diffusion.